2022
DOI: 10.3390/antiox11122388
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidants—A Critical Review on In Vitro Antioxidant Assays

Abstract: Antioxidants have been widely studied in the fields of biology, medicine, food, and nutrition sciences. There has been extensive work on developing assays for foods and biological systems. The scientific communities have well-accepted the effectiveness of endogenous antioxidants generated in the body. However, the health efficacy and the possible action of exogenous dietary antioxidants are still questionable. This may be attributed to several factors, including a lack of basic understanding of the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 159 publications
1
51
0
3
Order By: Relevance
“…However, Hernández-Fuentes showed that the salinity stress caused a decrease in the antioxidant capacity of bioactive compounds as well as antioxidant capacity (total phenol content) in tomato fruits during the development of plants . Thus, we further investigated the characterization of major phenolics using targeted analysis as it is well documented in the literature that phenolic compounds exhibit significant antioxidant capacity. …”
Section: Resultsmentioning
confidence: 99%
“…However, Hernández-Fuentes showed that the salinity stress caused a decrease in the antioxidant capacity of bioactive compounds as well as antioxidant capacity (total phenol content) in tomato fruits during the development of plants . Thus, we further investigated the characterization of major phenolics using targeted analysis as it is well documented in the literature that phenolic compounds exhibit significant antioxidant capacity. …”
Section: Resultsmentioning
confidence: 99%
“…This is because the antioxidant components in whole milk are dominated by casein (including the α‐, β‐ and κ‐type) and secondary‐derived peptides (Akan, 2020). In addition to fat‐soluble antioxidants, deproteinised milk contains only trace amounts of water‐soluble antioxidant components such as vitamins and uric acid (Kotha et al ., 2022). Moreover, all subunits of casein have the ability to inhibit Fe‐induced peroxidation of arachidonic acid in multi‐lamellar liposomes composed of dipalmitoyl phosphatidylcholine.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonols can help renew antioxidants such as vitamin C and vitamin E in the body [ 125 ]. Vitamins C and E are key antioxidants that may protect cells from oxidative stress, and flavonols have been shown to boost their levels in the body while also improving their antioxidant activity [ 81 , 105 ]. Flavonols can also stimulate the production of antioxidant enzymes such as superoxide dismutase (SOD) and catalase in the body [ 22 , 81 ].…”
Section: Main Textmentioning
confidence: 99%